Transcriptome and metabolome analyses reveal new insights into the regulatory mechanism of early embryoless seed development in rice - Shengjie Liu; Jingjing Peng; Wenhu Zhang; Jun Liu (BMC Plant Biology)
Abstract Background Embryo development holds a pivotal position in the ontogenesis and morphogenesis of rice plants, exerting a direct influence on plant growth and ultimately determining rice yield. Glutaredoxin, an abundant oxidoreductase, plays a crucial role across many facets of plant growth. Our research has uncovered that OsGrxC2.2 impacts rice embryo development, leading to embryonic abnormalities or the production of embryoless seeds, with an embryoless rate now approximating 80%. Consequently, we employed the OsGrxC2.2 overexpression line (OE11) as a model to dissect the regulatory mechanisms underlying the early development of embryoless seeds through comprehensive transcriptome and metabolome analyses. Results In this study, overexpression of OsGrxC2.2 in the Nipponbare (Nip) background resulted in smaller embryos and embryoless seeds, suggesting its potential broad regulatory role in embryoless seed formation. Transcriptome analysis revealed that OsGrxC2.2 overexpression altered the expression of seed development-related genes. Metabolite profiling during early seed development showed sustained upregulation of amino acids and nucleotides across three stages, whereas flavonoids, organic acids, and phenolamides exhibited transient upregulation followed by downregulation. Conversely, lipids and phytohormones were downregulated, which may be significantly correlated with embryo abnormalities and embryoless seed development. Integrated omics analyses highlighted the potential involvement of amino sugar and nucleotide sugar metabolism, linoleic acid metabolism, and zeatin biosynthesis in embryoless seed formation. Key metabolites (UDP-Glc, trehalose-6P, 9-cis,11-trans-octadecenoate) and their associated genes (OsTPP, OsLOX, OsCKX) were identified as potential critical regulators. Plant hormone assays further confirmed reduced cytokinin (CK) levels in embryoless seeds compared to wild-type seeds, supporting the role of zeatin biosynthesis in this process. Conclusions OsGrxC2.2 could modulate embryoless seed formation by influencing amino sugar and nucleotide sugar metabolism, linoleic acid metabolism, and zeatin biosynthesis. Investigations into early embryoless seed development may enhance our understanding of the regulatory network of embryoless seed development in rice. However, the detailed molecular mechanisms underlying this regulation require further investigation.